2018
DOI: 10.1536/ihj.18-046
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Mutations in <i>FBN1</i> and <i>TGFBR2</i> in Patients with the Syndromic Form of Thoracic Aortic Aneurysms and Dissections

Abstract: There are many inherited disorders associated with thoracic aortic aneurysms and dissections (TAADs), like Marfan syndrome and Loeys-Dietz syndrome (LDS). The 4 patients in this study all had TAADs and were initially diagnosed with suspected Marfan syndrome. We collected peripheral blood samples from the patients and their family members and then attempted to identify the causal mutation using different methods including PCR, Sanger sequencing, and next generation sequencing. We identified 3 novel heterozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Three other FBN1 -associated diseases were placed in ranks 2–4. Clinical and molecular data were simulated according to patient 1 in Cao et al 33 . The HPO terms are shown in panel (b).…”
Section: Resultsmentioning
confidence: 99%
“…Three other FBN1 -associated diseases were placed in ranks 2–4. Clinical and molecular data were simulated according to patient 1 in Cao et al 33 . The HPO terms are shown in panel (b).…”
Section: Resultsmentioning
confidence: 99%
“…Whether the incidence of gene mutation associated with Marfan syndrome or AD is higher in Chinese patients than in patients from western countries deserves further study. However, a recent study by Cao, et al 13) shed some light on this issue, who identified three novel heterozygous mutations in four Chinese patients with suspected Marfan syndrome, which indicated that some mutations associated with Marfan syndrome or AD might be ethnicspecific. Another distinct feature in our study was the relatively higher proportion of male patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies report somatogonadal mosaicism in other HCTD, for example in Loeys–Dietz syndromes [ 17 , 18 ] and vEDS [ 14 ]. We report here, to our knowledge, the first patient with a somatogonadal mosaicism in COL5A1 responsible for the cEDS diagnosed in his son.…”
Section: Discussionmentioning
confidence: 99%
“…Mosaicism has been reported in other genes of HCTD, in particular in Loeys–Dietz syndrome with mosaic variants in TGFBR1 and TGFBR2 [ 17 , 18 ]. We therefore, reviewed all affected individuals for other HCTD genes but also familial thoracic aortic aneurysm/dissection (FTAAD) genes studied in our center.…”
Section: Introductionmentioning
confidence: 99%